Prevention practices of hepatitis B virus and its associated factors among barbers in East Gojjam Zone, Northwest Ethiopia - Amlak, Baye Tsegaye; Lake Mengistie, Benalfew; Teshale, Seblework Abraham (Frontiers in Public Health, 2025)
IntroductionBarber-related infections, including hepatitis B virus (HBV), continue to be a major cause of illness and death. Numerous beauticians use razors and scissors on multiple customers without adequately sanitizing these tools. There is a lack of published research on the prevention practices and associated factors of hepatitis B virus infection among barbers in Ethiopia. Therefore, this study aimed to assess the practice and associated factors of hepatitis B virus infection among barbers.MethodA cross-sectional study was carried out involving 411 barbers selected through simple random sampling. Data collection was performed using an interviewer-administered questionnaire and an observational checklist. The collected data were first cleaned and entered into EpiData version 4.6 and then exported to SPSS version 25 for analysis. Model fitness was assessed using the Hosmer–Lemeshow test, and multicollinearity was evaluated with the variance inflation factor. A binary logistic regression model was employed for the analysis. To address confounding factors, explanatory variables with a p-value of less than 0.25 in the bivariable logistic regression were included in the multivariable logistic regression analysis. Factors with a p-value of less than 0.05 in the multivariable analysis were considered statistically significant.ResultsAmong the 411 participants, 328 (79.8, 95% CI: 75.6–83.6%) exhibited unsafe hepatitis B virus infection prevention practices. Unsafe practices were significantly associated with barbers who could not read or write (AOR 3.75, 95% CI: 1.39–10.12); primary and secondary education (AOR 3.44, 95% CI: 1.89–6.27) compared to those with college education and above; not using ultraviolet sterilizers (AOR 2.85, 95% CI: 1.30–6.27); insufficient knowledge (AOR 4.23, 95% CI: 2.13–8.40); unfavorable attitudes toward infection control (AOR 2.40, 95% CI: 1.34–4.31); and working hours of less than 8 h (AOR 0.27, 95% CI: 0.15–0.50).ConclusionNearly four-fifths of barbers exhibited unsafe practices in preventing hepatitis B virus infection. Low education levels, not utilizing UV sterilizers, lack of knowledge, working fewer hours, and negative attitudes toward infection prevention were all strongly associated with unsafe practices in the prevention of hepatitis B virus among barbers. Consequently, these findings underscore the need for targeted educational programs, improved access to sterilization tools, and policy changes to promote safer practices.